Kernel density estimation of egg attachment areas aids in revealing spatiotemporal changes in Chinese sturgeon spawning grounds - Pengsheng Li; Xuan Ban; Jinming Wu; Hui Zhang; Junyi Li; Li Shen; Zhigang Liu; Hao Du (Water Biology and Security)
Identifying precise egg attachment areas and tracking trends of spawning magnitude (total amount of spawned eggs) are critical for accurate habitat assessment and effective conservation efforts, especially for lithophilic spawning fishes. However, accurate measurement of spawning conditions across both spatial and temporal dimensions poses significant challenges. We conducted a fourteen-year field study below the Gezhouba Dam, the main spawning ground for the Chinese sturgeon, using Kernel Density Estimation (KDE) method and Catch per Unit of Effort (CPUE) to refine knowledge on egg attachment areas relative to previous assessments. In addition, our analysis documented shifts in spawning locations within these four areas over the past fourteen years, revealing a worrying trend of decreasing spawning magnitude. This approach not only enabled the incorporation of the density distribution of eggs into the assessment of spawning magnitude trends, but also underscored the potential of the KDE as a framework for identifying egg attachment areas and estimating spawning magnitude trends. Our results provide valuable insights into spawning degradation of Chinese sturgeon and inform conservation strategies to protect their fragile spawning grounds.